Pendidikan Iman dan Islam yang Kuat Serta Pengaruhnya dalam Membentuk Kepribadian - Alhafiz Hertri Anggara; Hanif Fajrul Hayatullah; Muhammad Syadaffa; Firas Afif (Reflection : Islamic Education Journal, 2025)
Education is a process of personality formation that results from the learning process. Through educational institutions, it is expected not only to prepare individuals to face an increasingly technological society of the future but also to influence the process of forming and developing human attitudes and behaviors. The purpose of this research is to analyze the role of Islamic education in shaping the character of quality Muslim individuals and to explore effective methods and approaches in that educational process. The method used in this research is a qualitative method with a literature study approach, where the author collects and analyzes various relevant literature regarding Islamic education and personality character. The results of this research indicate that ideal Islamic education not only focuses on academic aspects but also on the development of character and moral values in students, thereby producing individuals who are not only intellectually capable but also possess good morals and are beneficial to society. Ideal education is believed to serve human growth in all aspects, including spiritual, intellectual, imaginative, and scientific dimensions. Therefore, this educational process should encourage these aspects towards virtue and the attainment of a fulfilling life through the formation of character. Through the development of Muslim personality character, it is hoped that it can produce good, moral, and quality individuals who are beneficial to themselves, their families, their communities, their nation, and humanity in general.